Preparation of thermal transfer ink using disperse fluorescent yellow 82 for polyester substrates. Issue 2 (25th February 2014) - Xiu, Yufei; Shen, Qiankun; Fan, Fei; Wang, Chaoxia
Abstract : Purpose: – A disperse fluorescent yellow paste was mixed with a dispersant naphthalene sulfonic derivative via wet grinding process to prepare thermal transfer ink with good fluorescence. The paper aims to discuss these issues. Design/methodology/approach: – The surface tension, viscosity, pH value, zeta potential, stability and the morphology of ink samples were tested after the storing process. Findings: – The morphology of paste was homogeneous nearly spherical nanoparticles and the particle size was about 100 nm from the transmission electron microscopy (TEM), which was similar to the average particle size obtained from the particle size analyser. Research limitations/implications: – The paste particle size was 126.8 nm after storing at 50°C for one week. The addition of diethylene glycol was conducive to high fluorescent reflectivity and gave good line image quality both in warp and weft directions due to the low viscosity. Inkjet printed polyester fabrics achieved excellent rubbing, laundering and thermal subliming fastnesses. Originality/value: – The polyester fabrics thermal transferred with the ink contained diethylene glycol represented higher fluorescent reflectivity and gave better line image quality both in warp and weft directions. The inkjet printed polyester fabrics showed excellent colour reproducibility and all the fastnesses, including rubbing, laundering and thermal subliming, were higher than Grade 4.